Building mechanism of trusted virtual domain via the VPE - Li-na WANG; Hao ZHANG; Rong-wei YU; Han-jun GAO; Ning GAN (Tongxin xuebao)
Due to lack of flexible networking control,most exiting trusted virtual domain deployment approaches fail to provide elastic and secure interconnection.A trusted virtual domain architecture TVD-VPE was proposed in cloud com-puting enterprises which greatly enhances sensitive data protection.TVD-VPE constructs a virtual private ethernet based on separate device driver,VPE captures network packets at the backend driver and checks whether the packets comply with border security strategy,and data frames are encrypted among trusted virtual domains to ensure the security of sensi-tive data.Simultaneously,four protocols were proposed,TVDJOP/TVDEXP protocol for any new VM joining in or exit-ing TVD securely,TVDMP protocol for deploying border cross-domain access.Finally,the prototype system and tests of its functionality and performance were implemented.The experiment results reveal that the architecture can effectively prevent unauthorized access between these trusted virtual domains,while introduces little overhead to Xen network performance.